Empires and protection: making interpolity law in the early modern world*. Issue 1 (8th February 2017) - Benton, Lauren; Clulow, Adam
Abstract: References to protection were ubiquitous across the early modern world, featuring in a range of transactions between polities in very different regions. And yet discourses about protection retained a quality of imprecision that makes it difficult to pin down precise legal statuses and responsibilities. It was often unclear who was protecting whom or the exact nature of the relationship. In this article, we interrogate standard distinctions about the dual character of protection that differentiate between 'inside' protection of subjects and 'outside' protection of allies and other external groups. Rather than a clear division, we find a blurring of lines, with many protection claims creatively combining 'inside' and 'outside' protection. We argue that the juxtaposition of these 'inside' and 'outside' meanings of protection underpinned the formation of irregular, interpenetrating zones of imperial suzerainty in crowded maritime arenas and conflict-ridden borderlands across the early modern world.